Hydrothermal synthesis of multiwalled TiO2 nanotubes and its photocatalytic activities for Orange II removal - Zulfiqar, M. (Taylor and Francis Inc., 2018)
The solvothermal synthesis of multiwalled TiO2 nanotubes (MWTNTs) with the reaction of titanium dioxide (TiO2) nanoparticles and sodium hydroxide aqueous solution at moderate temperature is presented. The kinetic and isotherm studies were investigated for Orange II removal mechanism. MWTNTs were prepared in length 70â200Â nm, average diameter 4â10Â nm, and inter-shell spacing 0.78Â nm. Different characterizations were performed to confirm anatase and mesoporous structure of MWTNTs. An improvement in properties as compared to commercial TiO2 was observed; specific surface area 244.81Â m2/g and band gap 3.0Â eV. An excellent photocatalytic activity for Orange II removal was exhibited using synthesized MWTNTs. Â© 2018 Taylor & Francis.